UPAYA CINA DALAM MENINGKATKAN EKSPOR BATIK KE INDONESIA SETELAH ASEAN CHINA FREE TRADE AGREEMENT 2010 - Dwijayanti, Cicilia Septi; Priadarsani, Ni Wayan Rainy; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This research explains the increase of Chinese batik exports to Indonesia after ACFTA 2010-2018.This study theoretically uses the conceptual framework of the competitive advantage of the Diamond Model from Michael E. Porter. The competitive advantage of batik products is an important factor for China in the bilateral trade between Indonesia and China in the ACFTA framework.Competitive advantage known as the Theory of the National Competitive Advantage of Industries. Its specially based on competitive strength analysis in the competition of the Chinese batik industry in the batik market share in Indonesia, the competitiveness factor determines the success of Chinese businesses in an effort to increase the export of Chinese batik to Indonesia. The increase in Chinese batik exports to Indonesia after the enactment of ACTA in 2010-2018. Chinese batik products having several competitive advantages compared to Indonesian batik products. Keywords: Chinese batik, competitive advantage, free trade agreement